2010
DOI: 10.1111/j.1742-4658.2010.07794.x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous oxidative stress induces Ca2+ release in the yeast Saccharomyces cerevisiae

Abstract: The Ca2+‐dependent response to oxidative stress caused by H2O2 or tert‐butylhydroperoxide (tBOOH) was investigated in Saccharomyces cerevisiae cells expressing transgenic cytosolic aequorin, a Ca2+‐dependent photoprotein. Both H2O2 and tBOOH induced an immediate and short‐duration cytosolic Ca2+ increase that depended on the concentration of the stressors. Sublethal doses of H2O2 induced Ca2+ entry into the cytosol from both extracellular and vacuolar sources, whereas lethal H2O2 shock mobilized predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…2F) in a concentration-dependent manner, with a similar range between 0.2 and 5.0 mM (Fig. 2G), as reported by Popa et al (59). The level of responses was not saturated within the range of the tested H 2 O 2 concentration.…”
Section: Trpgz Is a Trp Channel Homolog In The Fungal Vacuolar Membrasupporting
confidence: 69%
“…2F) in a concentration-dependent manner, with a similar range between 0.2 and 5.0 mM (Fig. 2G), as reported by Popa et al (59). The level of responses was not saturated within the range of the tested H 2 O 2 concentration.…”
Section: Trpgz Is a Trp Channel Homolog In The Fungal Vacuolar Membrasupporting
confidence: 69%
“…In fact, an excessive elevation in [Ca 2 + ] i under stress conditions is known to cause apoptosis-like cell death in yeast 32 . Thus, we measured quantitatively the change in [Ca 2 + ] i using aequorin to (Fig.…”
Section: Msy1 Regulates [Ca 2 + ] I Increase On Hypo-osmotic Shockmentioning
confidence: 99%
“…Previous studies have indicated that both Cch1p and Yvc1p respond to oxidative stress (Popa et al, 2010). To determine whether the responses of Cch1p and Yvc1p to oxidative stress followed similar patterns, we investigated the influx of Ca 2+ into the cytoplasm during activation using individual deletions of these transporters, thereby ensuring that any interference could be eliminated.…”
Section: Cch1p Activation Under Oxidative Stressmentioning
confidence: 99%
“…Although Cch1p shows significant sequence and structural homology to VGCCs, Ca 2+ movement through Cch1p is not voltage dependent (Martin et al, 2011). Studies on Cch1p have revealed that it responds to different stimuli that include a sudden increase in pH (Viladevall et al, 2004), exposure to mating pheromones (Iida et al, 1994;Muller et al, 2001), store-operated stress (D'hooge et al, 2015;Locke et al, 2000), endoplasmic reticulum (ER) stress (Hong et al, 2010;Locke et al, 2000) and oxidative stress (Popa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation